On Chebyshev Polynomials, Fibonacci Polynomials, and Their Derivatives - Yang Li (Journal of Applied Mathematics)
We study the relationship of the Chebyshev polynomials, Fibonacci polynomials, and their rth derivatives. We get the formulas for the rth derivatives of Chebyshev polynomials being represented by Chebyshev polynomials and Fibonacci polynomials. At last, we get several identities about the Fibonacci numbers and Lucas numbers.